Effects of Richardson and Biot number on double‐diffusive Casson fluid flow with viscous dissipation. Issue 2 (11th November 2021) - M. Chandrashekar, Kemparaju; Nandeppanavar, Mahantesh M.; Nagaraj, Raveendra; Madikiri, Sreelatha
Abstract: An analysis is done of the effect of Richardson and Biot number on double‐diffusive mixed convective Casson fluid stream with viscous dissipation on warmth and mass stream with convective limit conditions and radiating vertical plate. The R‐K method with shooting procedure is used to solve the transformed equations mathematically. The accuracy of the numerical procedure has been validated through a comparison of the current work compared with prior available results. The sheer surface stress, Nusselt, and Sherwood number are increased with enhancement in Prandtl number. The Biot number Βi > 0.1 is investigated and increasing Biot number is observed to enhance the friction coefficient, Nusselt, and Sherwood number are increased. The influence of pertinent constraints on distinct flow parameters is determined and analyzed through tables and graphs.